ChemInform Abstract: Direct Perfluoroalkylthiolation of Few Chalcogenols. Issue 39 (September 2016) - Glenadel, Quentin; Billard, Thierry
Abstract: The reactivity of fluoroalkylsulfenamide homologs with chalcogenols is studied which furnishes fluoroalkylthiochalcogenides.